House Harkonnen - Herbert, Brian; Herbert, Frank; Anderson, Kevin J., 1962- (2001)
House Atreides and the Bene Gesserit Sisterhood are targeted by the power-hungry Baron Vladimir Harkonnen, who enslaves several planets in his quest for control of the Known Universe, but Leto Atreides will protect his son Victor and his legacy as Duke at all costs.
Based on the Dune universe created by Frank Herbert.
Keywords: Dune (Imaginary place) -- Fiction; Science fiction